2018
DOI: 10.1074/jbc.ra118.003716
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of the HECT ubiquitin ligase NEDD4-2/NEDD4L is essential for polyubiquitin chain assembly

Abstract: Edited by George N. DeMartino The NEDD4-2 (neural precursor cell-expressed developmentally down-regulated 4-2) HECT ligase catalyzes polyubiquitin chain assembly by an ordered two-step mechanism requiring two functionally distinct E2ϳubiquitin-binding sites, analogous to the trimeric E6AP/UBE3A HECT ligase. This conserved catalytic mechanism suggests that NEDD4-2, and presumably all HECT ligases, requires oligomerization to catalyze polyubiquitin chain assembly. To explore this hypothesis, we examined the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…To unravel the precise role of the exosite during ubiquitin chain formation by E6AP will require further investigation. On a broader scope, understanding how the exosite promotes catalysis in different HECT ligases will likely also help to clarify the directionality of ubiquitin chain elongation, for which different models have been presented (9, 26, 32, 51, 54, 75, 76), as well as the functional consequences of oligomerization, which has emerged as an important regulatory theme and has been associated with the exosite in certain cases (39, 69, 7779).…”
Section: Discussionmentioning
confidence: 99%
“…To unravel the precise role of the exosite during ubiquitin chain formation by E6AP will require further investigation. On a broader scope, understanding how the exosite promotes catalysis in different HECT ligases will likely also help to clarify the directionality of ubiquitin chain elongation, for which different models have been presented (9, 26, 32, 51, 54, 75, 76), as well as the functional consequences of oligomerization, which has emerged as an important regulatory theme and has been associated with the exosite in certain cases (39, 69, 7779).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that ITCH interacts with GRA35 via its C2 domain, which is known for membrane binding as well as mediating protein oligomerization (43). Thus, one possibility is that GRA35 could mediate ITCH oligomerization, which further enhances the ubiquitin ligase activity (44) and promotes its binding to the substrates, potentially including proteins that modulate LEW rat NLRP1 stability. Alternatively, this binding event could initiate broader perturbations to host cell homeostasis that are ultimately integrated through the inflammasome response.…”
Section: Discussionmentioning
confidence: 99%
“…While it was found that this N-terminal extension also induces HECT-dependent oligomerization, the exact structural mechanisms used by many of the members in the HECT E3 ubiquitin ligase family that employ this modification remain only partially understood. Previous studies have also pointed out that the inclusion of the extended α-helices in-front of the HECT domain are necessary to perform structural analysis of the HECT domain that coincidentally also include highly conserved, essential residues that mediate HECT-dependent oligomerization [ 3 , 8 , 11 , 31 , 43 , 45 ]. Future studies are essential to examine the oligomerization and/or autoinhibition potential for the currently illusive members of the HECT E3 ubiquitin ligases.…”
Section: Discussionmentioning
confidence: 99%